MODIFIKASI MESIN PEMARUT SAGU MENGGUNAKAN RANTAI CHAIN SAW - Abdul Aziz; Yus Witdarko; Mega Ayu Yusuf (Faculty of Agriculture, Musamus University, 2022)
The purpose of this study was to modify the sago grater roller, determine the tool's effective capacity, calculate the wet sago starch yield, and compare it with an unmodified grater machine. This research used tool modification and experimental methods, including the stages of problem identification, refinement of ideas. Based on the results of the grating research using the Honda GX 160 gasoline motor 5.5 Hp 2200 rpm, the average value of the effective tool capacity is 117.68 kg/hour, and the yield of wet starch with an average yield of 26.64%. Making this sago grater machine costs 3,458,300.